PT PRAMBANAN KENCANA BERKOLABORASI DENGAN UMKM GO INTERNASIONAL - IJLAL SETYOVIYON; DJIOGERALD PAOKI; AGUS SALIM; BILLY TANOYO WIJAYA; WENSESLAUS SALIVIAN KUMARA (AIBPM Publisher, 2018)
Exports and imports are important factors in stimulating a country's economic growth. Exports and imports will increase a country's consumption capacity, increase world output and provide access to scarce resources and potential international markets for various export products without which the poor countries will not be able to develop activities and national economic life. The aim of the study was to help analyze exports, various examples of cases in the export import business. The exportimport business is an international business activity to achieve the competitive advantage of companies and even the nation in global competition, by continuing to develop competencies, professionalism, commitment and regulation that can be a competitive advantage in the export-import business. The research method used is descriptive analytical namely discussing a number of problems, and summarizing the information contained in the study and presenting it in the desired form. Primary data is collected by observing research objects and interviews directly at the object of research, while secondary data is obtained from books and other sources. Simultaneous test results show that exports, imports, and economic growth have a significant influence on exchange rates and purchasing power. The partial test results show that the export variable has a significant influence on the exchange rate, while the export and import variables also have a significant influence on purchasing power. The research objective of this study is to provide conclusions about the implementation of Business to Business Marketing (export system) and how to overcome the obstacles faced by PT Prambanan Kencana in marketing its export products.